2015
DOI: 10.1007/s11060-015-1880-4
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke in patients with gliomas at The University of Texas-M.D. Anderson Cancer Center

Abstract: Patients with gliomas are at risk of cerebrovascular accidents (CVA) with potential consequences on survival, function, and local tumor control. Our objective was to provide information about CVA in patients with gliomas and to estimate survival in this group. We reviewed all adult glioma patients with ischemic CVA at the University of Texas-M.D. Anderson Cancer Center from 2003 through 2014. We extracted demographic, clinical, imaging, treatment and outcome data. We used descriptive summary data and estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…These results are consistent with prior smaller studies that have also reported radiation vasculopathy and surgical injury to be common causes of stroke in the primary brain tumor population. (8, 10) However, the perioperative stroke rate in our cohort was less than in previous studies, perhaps because we included all primary brain tumor types (not just gliomas) and we excluded incidental strokes from our primary analysis. (810) We also found that patients with radiation vasculopathy had a non-significant trend towards a higher recurrent stroke rate.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These results are consistent with prior smaller studies that have also reported radiation vasculopathy and surgical injury to be common causes of stroke in the primary brain tumor population. (8, 10) However, the perioperative stroke rate in our cohort was less than in previous studies, perhaps because we included all primary brain tumor types (not just gliomas) and we excluded incidental strokes from our primary analysis. (810) We also found that patients with radiation vasculopathy had a non-significant trend towards a higher recurrent stroke rate.…”
Section: Discussionmentioning
confidence: 98%
“…(8, 10) However, the perioperative stroke rate in our cohort was less than in previous studies, perhaps because we included all primary brain tumor types (not just gliomas) and we excluded incidental strokes from our primary analysis. (810) We also found that patients with radiation vasculopathy had a non-significant trend towards a higher recurrent stroke rate. Prior research has shown that cervicocephalic radiation is a strong risk factor for cerebrovascular complications in children and adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…76,77 While stroke can be the first clinical manifestation of malignancy, 78 the majority of ischemic strokes occur in the postoperative period. 79,80 The diagnosis can often be challenging both clinically and radiographically. 81 Acute onset of neurologic deficits can suggest a vascular event, but the differential can include underlying tumor progression and cerebral edema, as well as seizure.…”
Section: Stroke Epidemiology and Presentationmentioning
confidence: 99%
“…In addition, asymptomatic strokes are also common and can be found in 15 to 22% of glioma patients. 77,80 Pathophysiology Atrial fibrillation, hypertension, hyperlipidemia, diabetes, and tobacco use remain common risk factors for ischemic stroke, irrespective of malignancy. However, conventional cerebrovascular risk factors can be absent in up to 40% of cancer patients.…”
Section: Stroke Epidemiology and Presentationmentioning
confidence: 99%